2000
DOI: 10.2527/2000.7892257x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of high-oil corn on growth performance, diet digestibility, and energy content of finishing diets fed to beef cattle.

Abstract: Sixty crossbred beef steers (initial BW = 412 kg) were used in a 83-d finishing study to determine the effect of feeding dry rolled high-oil corn on performance and total-tract digestibility of finishing diets. Steers were allotted by weight to the following dietary treatments: 1) control corn (C; 82% normal corn, 12% triticale silage), 2) high-oil corn (HO; 82% high-oil corn, 12% silage), and 3) high-oil corn formulated to be isocaloric to C (ISO; 74% high-oil corn, 20% silage). Total lipid content was 4.9% (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 22 publications
2
26
3
Order By: Relevance
“…This indicates that the poor performance of steers fed LLH-HOG oat diet can be attributed to reduced DMI and not to the fact that the oat grain was less energy dense than either the barley or corn. These results reflect that of Andrae et al (2000), who reported that in order for rate of gain to increase with increasing dietary energy density, voluntary feed intake must not decrease. It should be emphasized that had the LLH-HOG oat-fed cattle been finished to the original target end-point, it is likely that the calculated NE m and NE g content of the diet would be lower than that reported in Table 5 due to increased carcass fat deposition.…”
Section: Trialsupporting
confidence: 87%
See 1 more Smart Citation
“…This indicates that the poor performance of steers fed LLH-HOG oat diet can be attributed to reduced DMI and not to the fact that the oat grain was less energy dense than either the barley or corn. These results reflect that of Andrae et al (2000), who reported that in order for rate of gain to increase with increasing dietary energy density, voluntary feed intake must not decrease. It should be emphasized that had the LLH-HOG oat-fed cattle been finished to the original target end-point, it is likely that the calculated NE m and NE g content of the diet would be lower than that reported in Table 5 due to increased carcass fat deposition.…”
Section: Trialsupporting
confidence: 87%
“…Improved feed efficiency, particularly as a result of lower DMI and similar ADG, reduces the cost of gain in feedlots and can have a marked impact on profitability of feeding cattle. In the case of fat addition, the displacement of dietary carbohydrate by lipid greater in ME is responsible for the improvement in feed efficiency (Andrae et al 2000). As determined through animal performance, the improved feed efficiency was reflected in 4.9 and 6.9% higher calculated NE m and NE g values of the LLH-HOG oat diet (Table 3).…”
Section: Trialmentioning
confidence: 96%
“…Furthermore, the average daily gain of 1.50 kg/day was satisfactory. Additionally, these results are consistent with Aferri et al (2005) who reported the gain of 1.20 kg/day and similar to Beaulieu et al (2002) who reported 1.50 kg/day for 102 days unlike the highest average gain of 2.00 kg/ day reported by Andrae et al (2000).…”
Section: Animal Performancesupporting
confidence: 91%
“…The high average gain of 2.00 kg/day were reported by Andrae et al (2000) who fed 60 crossbred steers with 82.0% of corn + 12.0% of triticale silage, 82.0% of high oil corn + 12.0% of silage, and highoil corn which were formulated to be iso energetic to the control which had 74.0% of high oil corn + 20.0% of silage. On the other hand, Kazama et al (2008) reported gain of 1.30 kg/day from crossbred heifers (Bos taurus taurus vs. Bos taurus indicus) finished in feedlot with diets containing 22.0% of cotton seed hulls, 45.0% soybean hulls, 7.00% cotton seed meal, 23.5% of corn germ meal or rice bran, 0.80% of mineral salt, 0.80% limestone and 1.20% urea.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation